The Role of Husband in Overcoming Anxiety in Primigravida Pregnant Women in PMB Yuni Nur Astuti, S.Tr.Keb Sukoharjo - Rahmalia Ikawati; Hutari Puji Astuti; Wijayanti (LPPM Universitas Harapan Bangsa, 2024)
Pregnancy is a crucial phase in a woman's life, especially during the first pregnancy (primigravida), which is often accompanied by high anxiety. This study aims to explore the husband's role in alleviating anxiety in primigravida mothers at PMB Yuni Nur Astuti Sukoharjo. Through a descriptive qualitative approach, data was collected through in-depth interviews with primigravida mothers, their husbands, and midwives. The results show that emotional and practical support from the husband plays a significant role in reducing the mother's anxiety. This support includes attention, affection, assistance with household chores, and preparation for childbirth. The husband's support also creates a sense of security, enhances the mother's readiness for childbirth, and helps the mother maintain emotional balance during pregnancy. This study emphasizes the importance of the husband's active role in improving the well-being of the mother and fetus, and encourages the husband's involvement from the early stages of pregnancy to reduce the risk of complications. Therefore, a proactive and supportive husband can have a significant positive impact on the mental and physical health of primigravida mothers.